SCENIC SPEECH IN THE «NEW UKRAINIAN THEATRE»: SPECIFICITY OF FUNCTIONING - Burlutskyi, Andriy (Вісник КНУКіМ. Серія «Мистецтвознавство», 2016)
The paper identifies specificity of forming and functioning of scenic speech in the period of formation of the «new Ukrainian theatre», whose framework chronologically unites the «silver» era (the 1920s) and the Ukrainian soviet theatre (the political theatre of the 1930s–1950s, the theatre of war time, the theatre of aesthetic innovations of the 1950s–1960s, and the «searching» theatre of the 1970s–1980s).